2015
DOI: 10.1007/s40558-015-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Typology of senior travellers as users of tourism information technology

Abstract: The importance of senior travellers as a travel segment for the tourism industry is continuously increasing as the number of pensioners increases in the Western world. These new senior travellers differ from earlier generations in many ways, one of which has to do with the increasing use of information and communication technologies as part of their information search process. This study examines senior travellers as users of tourism information technology. A qualitative approach was adopted to provide insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 40 publications
2
19
1
2
Order By: Relevance
“…This is in line with previous research that older individuals are quite heterogeneous in their use of information technology for travel purposes (Pesonen et al, 2015b). There also seems to be a clear divide between the informants in how involved they are with social media for travel purposes as we were able to divide them into three groups -disinclined, opportunistic and 2.0 users.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is in line with previous research that older individuals are quite heterogeneous in their use of information technology for travel purposes (Pesonen et al, 2015b). There also seems to be a clear divide between the informants in how involved they are with social media for travel purposes as we were able to divide them into three groups -disinclined, opportunistic and 2.0 users.…”
Section: Discussionsupporting
confidence: 90%
“…Thébault et al (2013) found that older consumers prefer online sites that they know. This is also confirmed by Pesonen et al (2015b) who found that half of their older respondents prefer familiar and safe brands when looking for travel-related information online.…”
Section: Enablers and Barriers To Social Media Use In Travelsupporting
confidence: 62%
See 2 more Smart Citations
“…La literatura se ha centrado principalmente en (ver Tabla I): a) las motivaciones de viaje de los turistas senior (Ward, 2014, Le Serre et al, 2013Cheng y Wu, 2009;Boksberger y Laesser, 2009); b) los factores psicológicos Jang y Wu, 2006); c) las características de la experiencia (Batra, 2009;Hunter-Jones y Blackburn, 2007); d) las necesidades del servicio (Chen et al, 2013;Wang et al,. 2013) y las características sociodemográficas (Pesonen et al, 2015;Peral et al, 2013;Jang y Ham, 2009). Sin embargo, poco se ha investigado sobre la influencia de Internet y el tipo de producto adquirido en el mercado senior (Vigolo y Confente, 2013).…”
Section: Revisión De La Literatura Sobre El Efecto De Internet En El unclassified